1997
DOI: 10.3758/bf03205502
|View full text |Cite
|
Sign up to set email alerts
|

Perceiving the sex and identity of a talker without natural vocal timbre

Abstract: The personal attributes of a talker perceived via acoustic properties of speech are commonly considered to be an extralinguistic message of an utterance. Accordingly, accounts of the perception of talker attributes have emphasized a causal role of aspects of the fundamental frequency and coarsegrain acoustic spectra distinct from the detailed acoustic correlates of phonemes. In testing this view, in four experiments, we estimated the ability of listeners to ascertain the sex or the identity of 5 male and 5 fem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(42 citation statements)
references
References 26 publications
(37 reference statements)
1
41
0
Order By: Relevance
“…Schwartz and Rine (1968), for example, reported near-perfect judgments of talker sex from whispered vowels recorded from a small sample of men and women, and, using grade school-aged children as listeners, Bennett and Montero-Diaz (1982) reported reasonably accurate judgments of speaker sex for whispered vowels. Speaker sex can also be judged from isolated voiceless fricatives (Ingemann, 1968) and from sine wave replicas of short sentences (Fellowes, Remez, & Rubin, 1997). Sine wave replicas, being aperiodic, do not have pitch in the traditional sense.…”
Section: Listening Studiesmentioning
confidence: 99%
“…Schwartz and Rine (1968), for example, reported near-perfect judgments of talker sex from whispered vowels recorded from a small sample of men and women, and, using grade school-aged children as listeners, Bennett and Montero-Diaz (1982) reported reasonably accurate judgments of speaker sex for whispered vowels. Speaker sex can also be judged from isolated voiceless fricatives (Ingemann, 1968) and from sine wave replicas of short sentences (Fellowes, Remez, & Rubin, 1997). Sine wave replicas, being aperiodic, do not have pitch in the traditional sense.…”
Section: Listening Studiesmentioning
confidence: 99%
“…Is the perception of a talker's sex a prerequisite for individual identification? Fellowes et al (1997) addressed these questions using a second set of modified sex-neutral sinewave signals. Intertalker differences were completely eliminated from the tokens by rescaling the tone pattern of every talker to match the average formant values of all ten talkers.…”
Section: Independence Of Talker Identity and Talker Sexmentioning
confidence: 99%
“…The extent to which perception of talker identity is contingent on perception of talker sex was addressed directly by Fellowes et al (1997) using perceptual tests and different types of sinewave signals. The first set of sinewave tokens were the same sinusoidal replicas used in the current training experiments.…”
Section: Independence Of Talker Identity and Talker Sexmentioning
confidence: 99%
“…The F 0 and lower harmonics, along with other acoustic ingredients, contribute to the perception of pitch. 59,60 Psychophysical experiments have demonstrated that F 0 differences facilitate the ability to distinguish between competing vowels or sentences. [61][62][63][64][65][66] The perceptual benefit provided by F 0 separation is apparent in neural processing.…”
Section: Pitch Representationmentioning
confidence: 99%